2022
DOI: 10.3390/mi13101561
|View full text |Cite
|
Sign up to set email alerts
|

High Rate Deposition of Piezoelectric AlScN Films by Reactive Magnetron Sputtering from AlSc Alloy Targets on Large Area

Abstract: This paper reports on the deposition and characterization of piezoelectric AlXSc1-XN (further: AlScN) films on Si substrates using AlSc alloy targets with 30 at.% Sc. Films were deposited on a Ø200 mm area with deposition rates of 200 nm/min using a reactive magnetron sputtering process with a unipolar–bipolar hybrid pulse mode of FEP. The homogeneity of film composition, structural properties and piezoelectric properties were investigated depending on process parameters, especially the pulse mode of powering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The first three papers [ 5 , 6 , 7 ] address both the growth process optimization and high rate, large area deposition on commercial and industry-relevant substrates at Sc concentration x ≈ 0.27–0.3, which is currently regarded by industry and academia as a reasonable trade-off point, allowing enhanced device performance without suffering too much from metastability-related issues, such as phase separation, an uncontrollable amount of abnormally oriented grains (AOGs), and elemental segregation into Sc-rich and Al-rich domains. Pirro et al [ 5 ] utilize RF bias on the substrate to better understand the relationship between stress levels and the dielectric and ferroelectric properties of the films.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first three papers [ 5 , 6 , 7 ] address both the growth process optimization and high rate, large area deposition on commercial and industry-relevant substrates at Sc concentration x ≈ 0.27–0.3, which is currently regarded by industry and academia as a reasonable trade-off point, allowing enhanced device performance without suffering too much from metastability-related issues, such as phase separation, an uncontrollable amount of abnormally oriented grains (AOGs), and elemental segregation into Sc-rich and Al-rich domains. Pirro et al [ 5 ] utilize RF bias on the substrate to better understand the relationship between stress levels and the dielectric and ferroelectric properties of the films.…”
mentioning
confidence: 99%
“…It was also shown that the addition of an AlN seed layer has only a minor effect on the piezoelectric performance of thick AlScN films. Barth et al [ 7 ] demonstrate AlScN sputtering at a very high deposition rate of 200 nm/min and investigate the homogeneity of structural and piezoelectric properties as well as how they are affected by different growth parameters. In particular, a hybrid unipolar-bipolar pulse mode with an optimized ratio of S Unipolar = 90% was shown to aid in the formation of highly uniform films with good piezoelectric and ferroelectric performance.…”
mentioning
confidence: 99%